2007
DOI: 10.1071/sr06069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zeolite application on nitrate and ammonium retention of a loamy soil under saturated conditions

Abstract: Nitrogen (N) loss from irrigated cropland, especially in rice paddies, results in low N-use efficiency and groundwater contamination. Soil conditions that increase ammonium and nitrate ion retention alleviate these problems. Clinoptilolite, a naturally occurring zeolite with high-exchange capacity, may be used to absorb ammonium and retard excess leaching of nitrate. The objectives of this research were to determine the effects of different rates of Ca–K-zeolite application (0, 2, 4, and 8 g/kg soil) on pore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 9 publications
2
13
0
1
Order By: Relevance
“…According to the CDE model, application of 2, 4 and 8 g zeolite per kilogram soil increases 145.38, 172. 14 …”
Section: Nitrate Ion Leaching Calibration Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the CDE model, application of 2, 4 and 8 g zeolite per kilogram soil increases 145.38, 172. 14 …”
Section: Nitrate Ion Leaching Calibration Resultsmentioning
confidence: 97%
“…Two holes were built at 31 cm height; one of them was for input and other was for output of water. This way was made for steady state water flow on soil columns [14]. Before re-packing the soil in the columns, it has been passed through a 2-mm stainless steel screen.…”
Section: Experiments Descriptionmentioning
confidence: 99%
“…While denitrification occurs at high soil temperatures, nitrification is reported to take place mainly in the temperature range of 30-40 • C. Our previous research demonstrated that both DI and PRD strategies control soil temperatures at lower values and within the considered range (Karandish and Shahnazari, 2016). NO 3 − -N concentrations tend to be significantly higher than NH 4 + -N concentrations under favorable conditions for the nitrification process (Sepaskhah and Yousefi, 2007). Marschner (1995) reported that average annual NH 4 + -N concentrations are often 10-1000 times lower than NO 3 − -N concentrations in well-aerated agricultural soils.…”
Section: Hydrus-2d Simulationmentioning
confidence: 99%
“…(Note: Gas bubbles were observed exiting the permeameter outlet during column test 5.) Low‐cost, abundant, natural zeolite has been proven effective for removing NH 4 + from water via cation exchange processes (Booker et al 1996; Demir et al 2002; Sepaskhah and Yousefi 2007). Therefore, a two‐stage filter treatment system in which drainage water first flows through SMI (to convert NO 3 – to NH 4 + ) and then flows through zeolite (to remove the NH 4 + ) could be a feasible way for taking out inorganic nitrogen originally present in subsurface drainage waters.…”
Section: Resultsmentioning
confidence: 99%